1998
DOI: 10.1046/j.1365-3156.1998.00229.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of antifilarial IgG4‐ELISA to detect Brugia malayi infection in an endemic area of Malaysia

Abstract: SummaryOBJECTIVE To evaluate the usefulness of antifilarial IgG4 antibody assay in detecting B. malayi infection in a filaria endemic area in Malaysia. METHODS A sandwich ELISA using B. malayi soluble antigen was employed to detect antifilarial IgG4 antibodies in serum samples of 330 individuals who comprised 88 healthy individuals from nonendemic areas, 15 B. malayi microfilaraemic cases, 22 individuals with soil-transmitted helminthiases, 9 elephantiasis cases and 196 residents from a B. malayi-endemic area.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Recent studies have reported the use of recombinant antigens for the detection of filarial specific IgG4 subclass antibody for the detection of brugian (17)(18)(19) and bancroftian (22) infections. IgG4 antibody levels are significantly elevated in individuals with microfilaremia and the levels decline after treatment (12,17,24). Antibody assay based on IgG4 subclass would be useful to identify active filarial infection (7,9,17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have reported the use of recombinant antigens for the detection of filarial specific IgG4 subclass antibody for the detection of brugian (17)(18)(19) and bancroftian (22) infections. IgG4 antibody levels are significantly elevated in individuals with microfilaremia and the levels decline after treatment (12,17,24). Antibody assay based on IgG4 subclass would be useful to identify active filarial infection (7,9,17).…”
Section: Discussionmentioning
confidence: 99%
“…IgG4 antibody levels are significantly elevated in individuals with microfilaremia and the levels decline after treatment (12,17,24). Antibody assay based on IgG4 subclass would be useful to identify active filarial infection (7,9,17). However, total IgG antibody-based assay with high specificity could be used for diagnosis of individuals with active infection as well as clinical cases in travellers and expatriates, primary surveillance in areas of unknown endemicity, detection of early infection in childhood (26) and to monitor chemotherapeutic program for the GPELF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies assessing antibody prevalence of lymphatic filariasis have employed assays that use either soluble worm antigens or recombinant antigens [12,13,18-21]. These antigens may not bind to the same set of anti-filarial antibodies and probably display different cross-reactivities to antibodies against other infections.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to brugian parasites is determined by brugian specific IgG4 serology using recombinant antigens in ELISAs [13,14] or rapid-format assays (BmR1-Brugia Rapid ™ [15] and CELISA [16]) with up to 95% sensitivity in Mf-positive samples. The ELISA format using soluble worm antigen (SWA) was shown to be more sensitive compared to the rapid-format which could be due to the mixture of antigens used in the ELISA.…”
Section: Introductionmentioning
confidence: 99%